Association Analysis Between Genotype and Environment: Differentiation Between Cyclocarya paliurus Resources That Accumulate Triterpenoids - Sun, Caowen; Shang, Xulan; Fang, Shengzuo; Yang, Wanxia; Cao, Yanni; Ding, Haifen; Li, Xiaochun (Frontiers in Plant Science, 2022)
Cyclocarya paliurus is mainly distributed in subtropical areas of China. Its leaves are rich in beneficial triterpenoids that have bioactivities against human diseases including hyperlipemia, diabetes, and hypertension. In this study, data on the genetic diversity, distributing environment, and triterpenoids of Cyclocarya paliurus samples were collected from a wide area in China. The data covered 316 C. paliurus germplasms collected from 26 distinct populations. An association analysis between genotype and triterpenoids were carried out to describe triterpenoids accumulation pattern. On the basis of our analyses, we identified the important trend that genotypes with higher triterpenoid contents belonged to a unique genotype subgroup. The results showed that pterocaryoside B and pterocaryoside A significantly vary among the genotypic subgroups. In addition, the different genotypic subgroups showed distinct geographical distributing areas. These findings provide information about the relationship between genetic and environmental factors and how this affects triterpenoids accumulation. This information will be valuable for targeted breeding and for further germplasm selection of C. paliurus resources.